Visualisasi Aljabar Matriks sebagai Alat Bantu Pembelajaran - Ami Fauzijah; Ira Fitriani Widianingrum (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Visualization is one of the use of technology for learning process. This applicationused for matrix algebra which more complex calculated operation, to make the learningprocess more attractive and hence will motivate student to study more actively.Keywords: visualization, learning, matrix algebra